THE INFLUENCE OF SERVICE QUALITY AND PRODUCT QUALITY BSI GRIYA ON CUSTOMER LOYALTY THROUGH CUSTOMER SATISFACTION OF BANK SYARIAH INDONESIA CAPEM ISKANDAR MUDA IN MEDAN CITY - Nikmir Rohmiati; Arlina Nurbaity Lubis; Beby Karina Fawzeea Sembiring (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2024)
This research aims to determine and analyze the influence of service quality on customer satisfaction, the influence of BSI Griya product quality on customer satisfaction, the influence of service quality on customer loyalty, the influence of BSI Griya product quality on customer loyalty, the influence of customer satisfaction on customer loyalty, and the influence of service quality on customer loyalty through customer satisfaction, the influence of BSI Griya product quality on customer loyalty through customer satisfaction of BSI Capem Iskandar Muda in Medan City. This type of research is associative research with a quantitative analysis approach. The population and sample in the study amounted to 121 customers, using saturated sampling techniques. The data collection methods used are questionnaires, interviews and documentation studies, while the types and sources of data use primary data and secondary data. The data analysis method uses descriptive statistical analysis and Structural Equation Modeling Partial Least Squares (SEM-PLS). The results of this research show that service quality has a positive and significant effect on customer satisfaction, BSI Griya product quality has a positive and significant effect on customer satisfaction, service quality has a positive and insignificant effect on customer loyalty, BSI Griya product quality has a positive and insignificant effect on customer loyalty , customer satisfaction has a positive and significant effect on customer loyalty, customer satisfaction is able to significantly mediate the effect of service quality on customer loyalty, and customer satisfaction is able to significantly mediate the effect of BSI Griya product quality on customer loyalty.